DIPG-13. Immune profiling by RNA-seq deconvolution and single-cell sequencing reveal myeloid cell enrichment in DIPG tumor microenvironment. (3rd June 2022) - Zhu, Xiaoting; Mishra, Deepak; Kumar, Shiva Senthil; Mchugh, Todd; Lazow, Margot; Fouladi, Maryam; Drissi, Rachid
Abstract: Diffuse intrinsic pontine glioma (DIPG) remains an incurable disease with median overall survival <12 months despite decades of clinical trials investigating multimodal therapies. Immunotherapy represents a promising treatment paradigm which has been successfully used in other cancers. An adequate understanding of the tumor microenvironment and immunologic profile is essential to identify potential immunotherapeutic targets to inform immunotherapy design. Previous studies have shown that most DIPG tumors harbor low mutational burden compared to adult cancers and are characterized by a non-inflammatory microenvironment, limiting the development of immunotherapies in this disease. Our team's prior work similarly demonstrated that most DIPG tumors have an immunologically "cold" microenvironment, but a subset of tumors harbors a more inflammatory gene expression profile and/or higher mutational burden, with trends toward improved survival and favorable radiographic response to radiation. Here, we applied a deconvolution analysis using CIBERSORTx on bulk RNA-seq data from 28 DIPG patients' tumors paired with matched normal tissue specimens, to profile the immune microenvironment of DIPG and evaluate immune-related gene expression to determine percentages of different types of immune cells. Our results indicate that DIPGs have very limited lymphocyte infiltration. However, the infiltration of macrophages "M2-like" type cells and CD4 memory resting T cells were significantly higher in tumors compared to normal tissue samples. Similar results were found using single-cell RNA sequencing performed on biopsy and autopsy tissue, with less than 5% of total cells identified as immune cells. MHC I components were widely expressed in DIPGs with no significant difference between tumor and normal tissue. Expression of CD11B and CD68 were higher in tumor compared to normal tissue, suggesting enrichment of myeloid cells. Overall, deconvolution analysis of bulk RNA-seq can be used to profile DIPG tumors' immune microenvironment to aid in the thoughtful design of effective immunotherapeutic strategies for this disease.